Evaluation of tumor infiltrating lymphocytes in breast carcinomas - Shovana Karki; Sansar Babu Tiwari; Alina Basnet (Journal of Pathology of Nepal)
Background: Among the parameters that have a prognostic and/or predictive significance to therapeutic response, in the case of breast carcinoma, the study of tumor-infiltrating lymphocytes in breast carcinomas is emerging. The present study aimed to access the clinicopathological profiles of tumor-infiltrating lymphocytes in patients with primary breast carcinoma.